DESIGN OF EARTHQUAKE-RESISTANT STEEL STRUCTURE IN HANANDJOEDDIN AIRPORT TERMINAL, TANJUNG PANDAN - Jonathan, Melvin
Belitung is a city with enormous tourist attractions in Indonesia. To accommodate the increasing movement of tourists every year. The increasing movement of tourists every year needs to be accomodated. Hence, Hanandjoeddin Airport will be built. Hanandjoeddin Airport is an airport located in Tanjung Pandan, Kabupaten Belitung, Kepulauan Bangka Belitung. This airport is planned to have airplane take-off facilities with a runway length of 3000 meters and a terminal covering an area of 12,000 m2. The upper structure of Hanandjoeddin terminal consists of 2 floors with a total height of 25.5 meters. Using steel as construction material, the upper structural elements are designed as Steel Ordinary Moment Frame (OMF) and the roof structure elements are designed as space frame. Structural design is carried out using earthquake analysis including analysis of Response Spectrum Modal Analysis, story drift check, P-Delta effect, horizontal irregularities, vertical irregularities, and redundancy check. The structural elements designed will be checked in terms of element strength and serviceability iteratively based on Indonesian Codes (SNI), in such a way that the effective cross-section is satisfied. Furthermore, detailing will be carried out for each element of the structures which involve design of connection, ball joint, slab reinforcement, shear stud, coupling plate, base plate, pedestal column, and tie beam.